Peran Dinas Pertanian Dalam Pemberdayaan Petani Jagung di Kecamatan Tellusiattingnge Kabupaten Bone - Andri Nasri (Departemen Ilmu Pemerintahan Fisip Unhas, 2024)
This study aims to determine the Role of the Department of Agriculture in Empowering Corn Farmers in Tellusiattingnge District, Bone Regency. The research method used is qualitative research and the number of informants is 12 people. This study uses data analysis techniques consisting of: data reduction, data presentation, and drawing conclusions. The results of this study indicate that the Bone District Agricultural Service has carried out empowerment by carrying out counseling and coaching programs, providing infrastructure and facilities, as well as monitoring and evaluation in accordance with the stages in the empowerment process according to Bone Regent Regulation Number 69 of 2017. For Tellusiattingnge District there are three the villages that are centers of corn cultivation according to the highest level of corn production in the Tellusiattingnge District are: Ulo Village, Pongka Village, and Palongki Village. Seeing the potential possessed in Tellusiattingnge Subdistrict for corn plantations, it is necessary to empower the government in a sustainable manner by conducting counseling and coaching, providing infrastructure and facilities, as well as monitoring and evaluation in collaboration with farming communities in order to create the lives of farming communities, especially superior and prosperous corn farmers.